Health-Related Quality of Life and Quality of Sexual Life in Obese Subjects. (23rd February 2014) - Poggiogalle, Eleonora; Di Lazzaro, Luca; Pinto, Alessandro; Migliaccio, Silvia; Lenzi, Andrea; Donini, Lorenzo M.
Abstract : The increased prevalence of obesity represents, currently, one of the major public health issues, due to its consequences on physical and psychological health status as well as on the psychosocial functioning. As defined by the World Health Organization, sexual health is "a state of physical, emotional, mental, and social well-being in relation to sexuality." The aim of the present study was to explore the relationship between sexual life in obese subjects and quality of life, psychological status, and disability. Methods . 95 obese subjects were recruited from June 2012 to February 2013 and underwent physical examination and measures for the assessment of quality of life, sexual life, psychological status, and disability. Results . In obese subjects sexual life was related to gender, age, psychological status, disability, and quality of life. Conclusion . As obesity is a multifactorial disease, and is accompanied by multiple comorbidities, it is difficult to identify a single causative factor responsible for the impairment of sexual life in obese subjects; thus, a thorough, multidimensional evaluation including sexual function assessment should be performed in obese people.